Validity and Reliability of the 30-s Continuous Jump for Anaerobic Power and Capacity Assessment in Combat Sport - Čular, Drazen; Ivančev, Vladimir; Zagatto, Alessandro M.; Milić, Mirjana; Beslija, Tea; Sellami, Maha; Padulo, Johnny (Frontiers in Physiology, 2018)
Cycling test such Wingate anaerobic test (WAnT) is used to measure anaerobic power (AP), but not anaerobic capacity (AC, i.e., the metabolic energy demand). However, in sports that do not involve cycling movements (Karate), the continuous jump for 30s (vertical jumps for 30s) has been extensively used to measure anaerobic performance in all young athletes. Limited information’s are available concerning its validity and reliability especially in children. As such, the current study aimed to test validity and reliability of a continuous jumps test (the CJ30s), using WAnT as a reference. Thirteen female Karate kids (age: 11.07±1.32 years; mass: 41.76±15.32 kg; height: 152±11.52 cm; training experience: 4.38±2.14 years) were tested on three separate sessions. The first and second sessions were used to assess the reliability using Intra-class correlation coefficient (ICC) of CJ30s, whereas on the third session WAnT was administered. Following CJ30s and WAnT, we assessed AP (1/CJ30s, as jump height [JH], fatigue index [FI], and blood lactate [BL]; 2/WAnT, as mechanical power [P], FI, and BL) and AC as the excess post-exercise oxygen consumption (EPOC). Large/highly significant correlations were found between CJ30s and WAnT EPOCs (r=0.730, P=0.003), and BLs (r=0.713, P=0.009). Moderate/significant correlations were found between CJ30s and WAnT FIs (r=0.640, P=0.014), CJ30s first four jumps mean JH and WAnT peak P (r=0.572, P=0.032), and CJ30s mean JH and WAnT mean P (r=0.589, P=0.021). CJ30s showed excellent and moderate reliability (ICC) for AP (maximal JH 0.884, mean JH 0.742, FI 0.657, BL 0.653) and AC (EPOC 0.788), respectively. Correlations observed especially in terms of AC between CJ30s and WAnT provide evidence that former may adequately assess anaerobic performance for the young combat athlete. CJ30 is a reliable test and allow an easy assessment of AP and AC in karate children.